Integrasi Nilai-Nilai Moderasi Beragama Dalam Mengembangkan Kurikulum Pendidikan Agama Islam - Nina Ayu Puspita Sari; M. Nasor; Rendra Nasrul Rifai; Esen Pramudya Utama; Raicha Oktafiani (Departement of Mathematics Education, 2024)
This exploration expects to make sense of the reconciliation of strict balance in fostering the Islamic strict training educational program. This sort of examination is subjective with a library research approach. Research information comprises of information on strict control, educational plan improvement, PAI material from essential sources as pertinent books and diaries. Information assortment methods are completed utilizing documentation. The scientists' information sources were gotten from books and diaries about strict control, educational plan improvement, PAI materials. Information investigation utilizes Content Examination. In view of the portrayal over, the creator reaches the determination that strict control is an